The strategy of construction equipment energy-saving control - Jiejia LI; DaiYan LIU; Rui QU (Institute of Advanced Engineering and Science, 2012)
To improve building energy-saving equipment control gets more and more attention. In order to make the room have a good comfort level, this paper designed a system to control temperature and humidity of variable air volume air conditioning, by a new control method of VAV air conditioning self-adaption decoupling to decouple temperature and humidity, combining the fuzzy PID control and the RBF neural network decoupling control method, improved the control effect that inhibit the coupling of temperature and humidity. Simulation results show that: the neural network decoupling control method has a strong decoupling control capability for the strong coupling lead to control issues like accuracy is not high and the control performance is not good in the multi-variable control system, stable state and dynamic performance have been improved and the control effect of the air-conditioning systems and indoor air quality have improved. DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.860